Bioremediation of wastewater using various sorbents and vegetable enzymes - Yadav, Anu (Research in Biotechnology, 2015)
The world community is facing a problem related to the management of wastewater very severely due to the extensive industrialization, increasing population density and a highly urbanized society. The quality of wastewater effluents is responsible for the degradation of receiving water bodies, such as lakes, rivers, streams. The two main processes for the removal of impurities from wastewater influents are chemical and biological. Because of the many drawbacks of chemical wastewater treatment, biological treatment is advocated in the last few decades. In this paper, an attempt has been made to use various alternative, inexpensive sorbents like sugarcane bagasse, spent tea leaves, fly ash and peroxidase enzyme isolated from the waste of vegetables to help in the bioremediation of wastewater samples. Among the various sorbents, fly ash was found to be the most effective and helped in the removal of organic matter as well as the inorganic ions. The combination of fly ash and charcoal helped drastically in lowering the chemical oxygen demand (COD) in the wastewater samples. Immobilized peroxidase enzyme was ideal for minimizing biological oxygen demand (BOD) and for the removal of phenols from wastewaters.